Caesarean birth by maternal request: a poorly understood phenomenon in low- and middle-income countries. Issue 1 (1st June 2020) - Harrison, Margo S; Garces, Ana; Figueroa, Lester; Esamai, Fabian; Bucher, Sherri; Bose, Carl; Goudar, Shivaprasad; Derman, Richard; Patel, Archana; Hibberd, Patricia L; Chomba, Elwyn; Mwenechanya, Miusaku; et al.
Abstract: Background: While trends in caesarean birth by maternal request in low- and middle-income countries are unclear, age, education, multiple gestation and hypertensive disease appear associated with the indication when compared with caesarean birth performed for medical indications. Methods: We performed a secondary analysis of a prospectively collected population-based study of home and facility births using descriptive statistics, bivariate comparisons and multilevel mixed-effects logistic regression. Results: Of 28 751 patients who underwent caesarean birth and had a documented primary indication for the surgery, 655 (2%) were attributed to caesarean birth by maternal request. The remaining 98% were attributed to maternal and foetal indications and prior caesarean birth. In a multilevel mixed effects logistic regression adjusted for site and cluster of birth, when compared with caesareans performed for medical indications, caesarean birth performed for maternal request had a higher odds of being performed among women ≥35 y of age, with a university or higher level of education, with multiple gestations and with pregnancies complicated by hypertension ( P < 0.01). Caesarean birth by maternal request was associated with a two-times increased odds of breastfeeding within 1 h of delivery, but no adverse outcomes (when compared with women who underwent caesarean birth for medical indications; P < 0.01). Conclusion: Caesarean performed by maternal request is more common in older and more educated women and those with multifoetal gestation or hypertensive disease. It is also associated with higher rates of breastfeeding within 1 h of delivery.